2011
DOI: 10.14214/df.119
|View full text |Cite
|
Sign up to set email alerts
|

Bark beetle-associated fungi in Fennoscandia with special emphasis on species of Ophiostoma and Grosmannia

Abstract: Global trade in untreated timber and wood products raises the risk of accidentally introducing forest pests and pathogens into new environments. Bark beetles (Coleoptera: Scolytinae) include several species that are regarded as forest pests. These insects are known to live in close association with fungi, especially species of ophiostomatoid fungi (Ascomycota). Several of these fungi are agents of blue stain in timber, and some are serious plant pathogens. However, only little is known regarding the fungal ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 197 publications
(220 reference statements)
1
48
1
Order By: Relevance
“…It appears that the fungus has a relatively specific association with this bark beetle species and its host tree. This apparently strict association has also been reported in several previous studies (Mathiesen 1950(Mathiesen , 1951Rennerfelt 1950;Mathiesen-Käärik 1953;Francke-Grosmann 1952, 1963aKäärik 1975aKäärik , 1980Villari 2012;Villari et al 2013 1989, 1991Kirisits et al 2000;Kirisits 2001Kirisits , 2004Bueno et al 2010;Stauffer et al 2001;Jankowiak et al 2007Jankowiak et al , 2009Linnakoski et al 2010;Linnakoski 2011;Jankowiak 2012;Repe et al 2013). For this reason, we re-examined some isolates from our previous studies identified as O. brunneo-ciliatum (Linnakoski et al 2010;Linnakoski 2011;Villari et al 2013 clavatum complex.…”
Section: Ipssupporting
confidence: 79%
“…It appears that the fungus has a relatively specific association with this bark beetle species and its host tree. This apparently strict association has also been reported in several previous studies (Mathiesen 1950(Mathiesen , 1951Rennerfelt 1950;Mathiesen-Käärik 1953;Francke-Grosmann 1952, 1963aKäärik 1975aKäärik , 1980Villari 2012;Villari et al 2013 1989, 1991Kirisits et al 2000;Kirisits 2001Kirisits , 2004Bueno et al 2010;Stauffer et al 2001;Jankowiak et al 2007Jankowiak et al , 2009Linnakoski et al 2010;Linnakoski 2011;Jankowiak 2012;Repe et al 2013). For this reason, we re-examined some isolates from our previous studies identified as O. brunneo-ciliatum (Linnakoski et al 2010;Linnakoski 2011;Villari et al 2013 clavatum complex.…”
Section: Ipssupporting
confidence: 79%
“…This study also revealed that the community of ophiostomatoid fungi associated with I. acuminatus in Ukraine appears to be rather different from that reported in other regions of Europe (Guérard et al, 2000;Linnakoski, 2011;Villari et al, 2013). The association between D. pinea and I. acuminatus, which is reported here for the fi rst time, is of considerable practical importance for forest health and requires further attention.…”
Section: Discussioncontrasting
confidence: 54%
“…L. truncatum was detected for the first time in Poland in this study. In Europe, this species is associated with root-feeding bark beetles on Scots pine (Gibbs and Inman 1991;Linnakoski 2011;Linnakoski et al 2012b;Wingfield and Gibbs 1991).…”
Section: And Inmentioning
confidence: 99%